Exploring institutional determinants of private equity and venture capital activity in Europe - Aleksandra Jandrić; Adam Geršl (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This paper examines the determinants of private equity activity across Europe. We analyze a total of 43 explanatory variables, categorized into six groups: Economy; Finance and capital markets; Quality of institutions; Life quality; Economic freedom and Globalization. We assess their impact on three target variables representing overall private equity activity: Investments, Divestments and Fundraising. The study covers 26 European countries over the period from 2007 to 2022. First, we use Bayesian Model Averaging (BMA) to identify which variables are essential for further analysis. We then conduct a multicollinearity test and remove variables highly correlated with those deemed significant by BMA. The final step involves panel data analysis to identify the key variables that countries should prioritize in order to enhance their private equity activity and make the necessary policy adjustments to improve their attractiveness in the private equity sector. Our findings highlight the significance of certain variables that have not been previously analyzed, alongside some traditionally acknowledged factors. Notably, trade openness, bank credit to the private sector, public spending on education, inflation and labor force emerge as significant determinants across Investments, Divestments, and Fundraising.
Keywords: C58; E44; G11; G24; G28; M13; O21; 330; Private equity; Venture capital; Fundraising; Investments; Divestments; Bayesian Model Averaging; Panel data analysis